Analisis Efisiensi Pelayanan Rawat Inap di Rumah Sakit Umum Dharma Yadnya di Era JKN - Farmani, Putu Ika; Dewi, Ni Made Umi Kartika (Bali International Scientific Forum, 2020)
Background: One of the hospital tasks is to provide inpatient services for JKN patients, including Dharma Yadnya Hospital. Inpatient efficiency analysis is needed to monitor the quality of hospital service quality using BOR, LOS, TOI, and BTO values. Objective: This study aims to determine the efficiency of inpatient services at Dharma Yadnya Hospital in 2011-2013 and 2014-2016. Method: Descriptive quantitative is used as the research design with a retrospective approach at the Dharma Yadnya General Hospital in December 2019. The observations of a recapitulation daily census inpatient of 2011-2016 data used as the data of this study and also the supporting data (SOP, HR (Human Resource), and facilities support) that was collected by interviewing medical records and inpatient staff. Inpatient efficiency analysis using Johnson's Barber chart and presented in tables, graphs, and narratives. Results: The results showed that throughout 2011-2016 there were no changes in SOP related to hospitalization with the number of HR ranged from 32-36 people per year. The trend of inpatient efficiency parameters for BOR and BTO has increased, but for LOS and TOI tends to decrease. Whereas for Barber Johnson's analysis, there was a tendency to approach the efficient regions in 2014-2016 (after JKN program implemented) compared to 2011-2013. Conclusion: There was no difference in the efficiency of hospitalization before and after the JKN program implemented. Based on these results the hospital management is expected to held reguraly evaluations using Barber Johnson chart method and monitor service quality to increase the promotion to improve inpatient efficiency.